A NARRATIVE REVIEW ON AUTOMATION AND DIGITALIZATION IN QUALITY CONTROL LABORATORIES OF PHARMACEUTICALS - Sheikh Abdul Khaliq; Muhammad Kashif; Muhammad Jiyad Shaikh; Ijaz Hussain (International Journal of Pharmacy & Integrated Health Sciences)
Background: The automation and digitalization of pharmaceutical quality control (QC) laboratories can enhance quality assurance. The adoption of automation and digitalization has improved the efficiency, productivity, and compliance of QC testing.Objectives: This review article aims to explore the integration of automation and digitalization technologies, including Full Laboratory Automation (FLA), Total Laboratory Automation (TLA), Artificial Intelligence (AI), the Internet of Things (IoT), and Machine Learning (ML). Methodology: The study investigated the potential of automation and digitalization in the QC department within the pharmaceutical industry—the data collected from various research studies conducted from 2015 to 2024, sourced from authentic scientific databases. The data were sequentially analyzed using specific inclusion and exclusion criteria to draw the findings. The GRADE criteria were used to check quality.  Results: The use of TLA has significantly bolstered the development of the QC department. For instance, Sysmex's TLA system enhances automation within QC procedures, leading to increased accuracy and reduced errors. Moreover, technologies like IoT-based monitoring systems, robotic sample handlers, and AI-based tools—such as AI-based pathogen detection systems—are being implemented. Utilization of these developments allowed for effective work and testing of a large number of samples. The advantages of TLA are cost-effectiveness, management of labor, maintenance prediction, and effective decision-making. Automation technologies and AI have helped reduce environmental impact by maximizing the use of resources and integrating green practices.Conclusion: Automation and AI-driven technologies enhance QC efficiency and ensure regulatory compliance, which may result in the production of quality products.